2016
DOI: 10.1038/srep31086
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of HDAC6 for activation of Notch1 by TGF-β1

Abstract: TGF-β1 is enriched in the tumor microenvironment and acts as a key inducer of epithelial to mesenchymal transition (EMT) in lung cancer. The NOTCH signaling pathway is conserved across species and is an essential pathway for development, cell differentiation, and cancer biology. Dysregulation of Notch signaling is a common feature of non-small cell lung cancer (NSCLC) and is correlated with poor prognosis. Crosstalk exists between the NOTCH and TGF-β signaling pathways in EMT. Herein we report that histone dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…After the NICD enters the cytoplasm, it is further translocated into the nucleus, where it binds to the DNA-binding protein CBF/RBP-JK to form a transcriptional activator and activates the downstream genes. In mammals, the main The effect of BMSC-CM on NSCs downstream target gene of Notch is Hes1 (Hairy/enhancer of split) and ESR gene family, such as Hes-1 and Hes-5 (Deskin et al, 2016). In this paper, we found that the expression of Notch1 and Hes1 were increased in H 2 O 2 treatment groups based on the results of the western blot when compared with the control groups, which was consistent with the previous findings (Ding et al, 2011;Tang et al, 2014;Khubutiya et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After the NICD enters the cytoplasm, it is further translocated into the nucleus, where it binds to the DNA-binding protein CBF/RBP-JK to form a transcriptional activator and activates the downstream genes. In mammals, the main The effect of BMSC-CM on NSCs downstream target gene of Notch is Hes1 (Hairy/enhancer of split) and ESR gene family, such as Hes-1 and Hes-5 (Deskin et al, 2016). In this paper, we found that the expression of Notch1 and Hes1 were increased in H 2 O 2 treatment groups based on the results of the western blot when compared with the control groups, which was consistent with the previous findings (Ding et al, 2011;Tang et al, 2014;Khubutiya et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The results, as shown in Figure 2A, revealed that the apoptotic rate was increased when H 2 O 2 treated the NSCs. In mammals, the main downstream target gene of Notch is Hes1 (Hairy/enhancer of split) and ESR gene family, such as Hes-1 and Hes-5 (Deskin et al, 2016). Consistent with the previous reports, these findings indicated that H 2 O 2 could simulate the oxidative stress environment and the apoptotic rate of cells increased along with an increase in concentration of H 2 O 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Such HSP90-inhibiting treatments resulted in depletion of the CSC fractions (CD44/ALDH double-positive cells) and downregulation of specific microRNAs associated with CSCs' resistance to chemotherapy [72]. Taken together, all these publications [65][66][67][68][69][70][71][72] testify the important role of HSP90 in forming the CSC phenotype through EMT, although there may be multiple HSP90-mediated mechanisms of triggering and promoting EMT in different types of cancer.…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoning mentioning
confidence: 91%
“…Using selective inhibitors of the HSP90 chaperone activity or techniques with HSP90 knockdown, it was shown that intracellular HSP90 can be conducive to EMT in carcinomas of different localization [65][66][67][68][69][70][71], while the mechanisms of such HSP90-dependent EMT may vary in different cases. So, intracellular HSP90 was reported to promote EMT via (i) activation of HIF1α and NFκB [65] and stabilization of an oncogenic nonhistone chromatin-binding protein high-mobility group AT-hook 2 (HMGA2) [66] in colorectal cancer cells, (ii) activation of the TGF-β1/Notch1 signaling [67] or anaplastic lymphoma kinase (ALK) signaling [68] in different variants of lung cancer, (iii) direct interactions with Twist1 to stabilize and activate the latter in hepatocellular carcinoma [69], (iv) stabilization of low-density lipoprotein receptor-related protein 5 (LRP5) followed by LRP5-mediated stimulation of Wnt/beta-catenin signaling in gastric cancer [70], and (v) activation of STAT3 followed by the Twist1 expression upregulation in ovarian, renal, and nasopharyngeal cancer [71].…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoning mentioning
confidence: 99%
“…Recent studies have demonstrated that Notch signalling plays an important role in lung cancer initiation via crosstalk with transcription factors enhancing epithelial-to-mesenchymal transition (EMT)31. Further, dysregulation of Notch signalling as a common feature of NSCLC correlating with poor prognosis has been associated with TGF-β and EMT32. Related to this, Notch1 related EMT promotion has been associated with an increased EpCAM expression33.…”
Section: Discussionmentioning
confidence: 99%